Interplay of information quantifiers and the modified Jaynes-Cummings model - Abdel-Khalek, Sayed (2011)
The dynamics of the Buck and Sukumar model (B. Buck and C. V. Sukumar, Phys. Lett. A 81, 132 (1981)) is investigated using different semi-classical information-theory tools. Their interplay reveals somewhat unexpected features. A new signature for the classical-quantum barrier is encountered thereby.